Alterations in the pulmonary histoarchitecture of neonatal mice exposed to hyperoxia - Renata B. Reis; Akinori C. Nagato; Clarissa R. Nardeli; Isadora C.P. Matias; Wanderson G. Lima; Frank S. Bezerra (Elsevier, 2013)
Objectives: To analyze the effects of exposure to hyperoxia (100% oxygen) on the lung histoarchitecture of neonatal mice. Methods: Neonatal Balb/c mice were exposed to hyperoxia (HG) (100% oxygen) (n = 10) in a chamber (15 x 20 x 30 cm) for 24 hours with a flow of 2 L/min. The control group (CG) (n = 10) was exposed to normoxia in the same type of chamber and for the same time. After exposure, the animals were euthanized by decapitation; the lungs were removed and processed for histological examination according to the laboratory routine. Three-mm thick sections were stained with hematoxylin and eosin (H&E). The morphometric analysis was performed with in order to analyze the macrophages present in the alveolar lumen, surface density (Sv) of gas exchange, volume density (Vv) of lung parenchyma, and areas of atelectasis. Results: A decrease in the number of alveolar macrophages (MØ) was observed in the HG (HG = 0.08 ± 0.01 MØ/mm2, CG = 0.18 ± 0.03 MØ/mm2, p = 0.0475), Sv of gas exchange in HG (HG = 8.08 ± 0.12 mm2/mm3, CG = 8.65 ± 0.20 mm2/mm3, p = 0.0233), Vv of lung parenchyma in HG (HG = 54.7/33.5/83.5%/mm2; CG = 75/56.7/107.9%/mm2, p < 0.0001) when compared with the CG. However, there was an increase in areas of atelectasis in HG (HG = 17.5/11.3/38.4 atelectasis/mm2, CG = 14/6.1/24.4 atelectasis/mm2, p = 0.0166) when compared with the CG. Conclusion: The present results indicate that hyperoxia caused alterations in lung histoarchitecture, increasing areas of atelectasis and diffuse alveolar hemorrhage. Resumo: Objetivos: Analisar os efeitos da exposição à hiperóxia (100% de oxigênio) sobre a histoarquitetura pulmonar de camundongos neonatos. Métodos: Camundongos neonatos da linhagem Balb/c foram expostos à hiperóxia (GH) (100% de oxigênio) (n = 10) em uma câmara (15 x 20 x 30 cm) por 24 h, com fluxo de 2 L/min. O grupo controle (GC) (n = 10) foi exposto a normóxia em um mesmo tipo de câmara e pelo mesmo tempo. Após a exposição, os animais foram sacrificados por decapitação, os pulmões foram removidos para análise histológica e processados de acordo com a rotina do laboratório. Cortes de 3 μm de espessura foram corados com hematoxilina e eosina (H&E). A análise morfométrica foi realizada com o objetivo de analisar macrófagos presentes na luz alveolar, densidade de superfície (Sv) de trocas gasosas, densidade de volume (Vv) de parênquima pulmonar e áreas de atelectasias. Resultados: Foi verificada diminuição do número de macrófagos alveolares (MØ) no GH (GH = 0,08 ± 0,01 MØ/mm2; GC = 0,18 ± 0,03 MØ/mm2; p = 0,0475), Sv de troca gasosa no GH (GH = 8,08 ± 0,12 mm2/mm3; GC = 8,65 ± 0,20 mm2/mm3; p = 0,0233), Vv de parênquima pulmonar no GH (GH = 54,7/33,5/83,5%/mm2; GC = 75/56,7/107,9%/mm2; p < 0.0001) quando comparado com o GC. Entretanto, houve aumento de áreas de atelectasias no GH (GH = 17,5/11,3/38,4 atelectasia/mm2; GC = 14/6,1/24,4 atelectasia/mm2; p = 0,0166) quando comparado com o GC. Conclusão: Nossos resultados indicam que a hiperóxia promoveu alterações na histoarquitetura pulmonar, aumentando áreas de atelectasia e hemorragia alveolar difusa. Keywords: Hyperoxia, Lung, Newborn animals, Palavras-chave: Hiperóxia, Pulmão, Animais recém-nascidos